Quadro Editorial (Estudos em Design, 2019)
Quadro EditorialEditoresCristina PortugalRita Maria de Souza Couto Avaliadores desta edição v. 27, n. 3 (2019) Alexandre Santos de OliveiraAlexandre FarbiarzÁlvaro José Barbosa SousaAna Veronica PazminoAndréa AlmeidaAndrea SousaAntonio Ferreira Colchete FilhoBárbara NecykBeany MonteiroCássia Letícia CarraraCristina PortugalDaniel PortugalDaniel RaposoDaniel Wyllie RodriguesGisela de CamposEdson Rufino de SouzaEloiza Andrade CorrêaFernanda AbreuFrederico BraidaHelena Barbosa Haroldo GalloIone BentzJackeline FarbiarzJuliana BuenoLuiz AgnerLuiza NovaesMarcos BragaMaria José JorenteMariana PaduaMariano Lopes de Andrade NetoMaristela Mitsuko OnoPaula LandimRaimundo DinizRanielder de FreitasRogério José CâmaraSandra Regina RechSandra SouzaSydney FreitasTomás BarataVirginia Borges Kistmann